Social network-based trustworthy routing in delay tolerant networks - YU Hai-zheng1; MA Jian-feng1; BIAN Hong3 (Tongxin xuebao)
A trustworthy routing protocol was proposed based on social networks for delay tolerant networks（DTN）,which ensured the messages to be sent to the destination node efficiently and reliably against more selfness nodes.With a method of relation evaluation among nodes in social networks,the relation intensity matrix between the groups was fig-ured out.The source node chose proper member nodes as next intermediate node to forward the messages according to the relation intensity matrix,which avoided the messages to be sent to the selfness nodes and reduced the probability of dropping the messages.At the same time,due to intermittent connectivity of DTN,a method of identity-based cryptogra-phy was introduced during the process of messages forwarding,it ensured the security of messages forwarding.The ex-periments show that our method can ensure the security and efficiency of messages to the destination.